Crônicas da pandemia: ecos do isolamento - Cociuffo, Tania (2023)
The beginning of the 21st century is marked by one of the most significant pandemics ever: the New Coronavirus. The effects of compulsory social isolation and fear of the virus, with its invisible nature, have been present since the World Health Organization declared a “state of pandemic”. This thesis aims to describe and interpret testimonies ― narrated here in chronicle form ― about the main impacts and emotional experiences experienced during the Coronavirus pandemic. These statements were prepared by a group of psychology students at a university in São Paulo, in the form of distance learning. To continue the mandatory basic internship, in the third year of graduation, we started with the following hypothesis: the use of narratives in chronicles and group sharing, as a teaching strategy within the scope of supervision, would allow not only the observation of everyday life ― intrinsic purpose of an observation discipline ―, but also the construction of meanings and the elaboration of the emotional repercussions of social isolation. This approach is justified by the nature of the chronicle, which, as a literary genre, explores everyday situations and personal experiences. We used psychoanalytic and quantitative methods, preserving the reservations of the Freudian method. Three axes guided the construction of this study: the pandemic, recognized as a highly relevant circumstance; the chronicles developed, used as a teaching resource; and extramural psychoanalysis, which also played a fundamental role. In a subsequent stage, a comparison was made between chronicles researched in Brazilian press newspapers about the Spanish Flu (1918) and the chronicles described in this thesis, with special attention to selected themes ― some of them, namely: everyday life, suffering psychic and subjectivity, and sociopolitical aspects. This analysis aimed to verify the emphasis found in the records of both historical events. Subsequently, the procedure was repeated with records of chronicles in the Brazilian press about COVID-19, categorizing them within the themes raised in this work to document the emphases in the researched contents identified in historical records. Furthermore, the comparison between the chronicles of the Spanish Flu and COVID-19 periods, written by the press, historically corroborates the difficulty of our government representatives in learning from past experiences. The writing and subsequent analysis of the chronicles of psychology students demonstrated that the teaching strategy adopted brought new meanings and possibilities for confronting the pandemic, social isolation and the great helplessness of all of us. This research results in attributing meaning to experience, using the psychoanalytic method based on listening ― reading ― and interpreting the chronicles, seeking an unconscious meaning through the conscious content. This thesis allows for a new connection of meanings through the researcher's floating attention, countertransference and free association